The Influence of Education and Communication Channels on Management Practices in Ghana Public Universities - Poku, Michael B. Adusei (Edusia: Jurnal Ilmiah Pendidikan Asia, 2023)
This study was conducted at C. K. Tedam University of Applied Sciences and Technology. It was guided by education and communication model as propounded by Shanon and Weaver (1949). This study was designed to investigate the influence of communication channels on education management practices in Ghanaian public universities. The study specifically investigated the types of communication channels used in the university and related the channels to the constraints faced in communicating messages in the university. Literature was reviewed in relation to the above stated objective. The study sample was drawn from CKT-UTAS and involved both academic and administrative staff. The sample size was one hundred and fifty two (152) which represents 77.6% of the target population. Stratified random sampling techniques based on the respondents’ job descriptions were used. The instruments for data collection involved use of questionnaires and information from secondary data materials for instance the University Act 2019, Act 1000 and the employee survey findings of 2006. Data was analyzed using descriptive statistics. The major findings revealed that CKT-UTAS had few channels of communication and that the communication policy framework was in place. However, the study identified that CKT-UTAS relies on Head of Departments, Group representatives, memos, notice boards, face to face and telephone to communicate. The study therefore, recommended that CKT-UTAS embraces new channels of communication (i.e. use of email) for efficiency purposes in addition to the already existing ones. Also the university should adopt strategies of enhancing communication between the staff and administration.